Non-spherical multi-oscillations of a bubble in a compressible liquid - Wang, Qian-Xi (2019)
Submitted by Jairo Amaro (jairo.amaro@sibi.ufrj.br) on 2019-06-14T17:17:40Z No. of bitstreams: 1 9-2015_Non-spherical-multi-oscillations-min.pdf: 293845 bytes, checksum: 96bce9ff9702ba30fb718d519108e659 (MD5)